RELATIONSHIPS BETWEEN PERCEIVED PRENATAL STRESS, COPING STRATEGIES, AND PREGNANCY OUTCOMES - Sanguanklin, Natthananporn; Buaboon, Natthapat; Nirattharadorn, Mayuree; Kamolwarin, Sudaporn; Poonlert, Hathaichanok; Baimonta, Lawan (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
The purposes of this descriptive correlational study were to: 1) assess the level of perceived prenatal stress among pregnant women; and 2) examine the relationships between perceived prenatal stress, coping strategies and pregnancy outcomes (gestational age, birth weight, and Apgar score at 5 minutes). The participants in this study were 128 pregnant women who had either been infected the Coronavirus 2019 or lived with an infected family member. They were recruited from antenatal care clinics at the public hospitals in Pathum Thani and Samut Prakan provinces. The research instruments consisted of 1) a personal information questionnaire; 2) the Thai version of the Perceived Stress Scale (T-PSS 10); 3) the Thai version of Brief COPE; and 4) a pregnancy outcomes data record form. The Cronbach’s alpha coefficients of the instruments were .78 and .84, respectively. Data were analyzed using descriptive statistics and Pearson correlation. The results showed that 95.3% of pregnant women had been infected the Coronavirus 2019 and 59.73% encountered financial difficulties during the pandemic. The mean perceived prenatal stress score was at a moderate level (M = 16.92, SD = 5.31). Perceived prenatal stress was significantly negatively correlated with emotion-focused coping strategies (r = -.23, p < .01) and significantly positively correlated with dysfunctional coping strategies (r = .35, p < .01). However, perceived prenatal stress was not significantly correlated with problem-focused coping strategies (r = .01, p > .05). Regarding pregnancy outcomes, the rates of preterm birth and low birth weight were 3.12% and 5.46%, respectively. All newborns had an Apgar score of 10 at 5 minutes. Perceived prenatal stress was not significantly correlated with gestational age at birth or infant birth weight (r = .06 and .07, respectively; p > .05). The findings suggested that perceived prenatal stress is correlated with each coping strategy in varying directions, with emotion-focused coping strategy being effective in reducing perceived prenatal stress among pregnant women in this study.